POSTMODERN LIBERALISM AND SOLIDARITY: RICHARD RORTY - Selim, Ferdi (PEOPLE: International Journal of Social Sciences, 2017)
“Multiculturalism”, “living together” and “cohabitation” are of universal issues at the moment. As known for most of us, alienation and estrangement are widespread as well. Even the existence of “other” is not tolerated sometimes. Initially, it must be stated that the scope of the problem is wider than it is presumed to be and cannot be solved through induction since the bigoted beliefs and the traditionalized habits are at the core. This common approach relies on having a sole list of truth lading, a sole definition of humanitarian status and a sole universal context of respective lives. The given concept of belief must be replaced with “contingency”. The individual with the conscience of contingencies gets rid of metaphysical and theological truths and be set free. The liberal societies of our century must produce much more people who are able to accept the contingency of vocabulary which is used to utter the utmost hopes – contingency of their conscience – and still remain loyal to commands of respective consciences.The present study aims at presenting a liberal, pluralist and contingent proposition for a solution in context with the given case. The proposition essentially based on the concepts which are spearheaded by Richard Rorty, a leading American intellectual, for postmodern liberal countries. Richard Rorty claims that the concept of “one of us” can be enlarged as such to include those who once were defined as “others”. In this respect, “us” is much more limited and local compared to human race. The sentiment of solidarity cannot be clarified enough through the approach of “just another human”. The mutual sharing and features of humans are effective in constituting the sentiment of solidarity as “one of us”. His given approach whose chief task is to encourage solidarity and being us is in an endeavor to forge a type of liberal ironist individual. The liberal ironist individuals who stand against suppression, be aware of contingency and be in a perpetual quest to realize them are the champions of solidarity and progress. Another significant task of this study is to investigate the probabilities of achieving Rorty’s given claims.